2014
DOI: 10.1186/1471-2393-14-353
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian birth place study: examining maternity care provider attitudes and interprofessional conflict around planned home birth

Abstract: BackgroundAvailable birth settings have diversified in Canada since the integration of regulated midwifery. Midwives are required to offer eligible women choice of birth place; and 25-30% of midwifery clients plan home births. Canadian provincial health ministries have instituted reimbursement schema and regulatory guidelines to ensure access to midwives in all settings. Evidence from well-designed Canadian cohort studies demonstrate the safety and efficacy of midwife-attended home birth. However, national rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
2
28
0
2
Order By: Relevance
“…Also, positive attitudes of midwives regarding home birth and a critical attitude to hospital birth for non-medical reasons have been found to explain some of the variance found in home birth rates across Dutch midwifery practices [32]. Positive attitudes towards home births among UK maternal caregivers in general, are associated with the amount of experience and confidence in managing obstetric risks in home births and with maternal caregivers’ beliefs about safety of home births [33]. Other interesting outcomes related to preferred place of birth and risk perception have been found as well.…”
Section: Introductionmentioning
confidence: 99%
“…Also, positive attitudes of midwives regarding home birth and a critical attitude to hospital birth for non-medical reasons have been found to explain some of the variance found in home birth rates across Dutch midwifery practices [32]. Positive attitudes towards home births among UK maternal caregivers in general, are associated with the amount of experience and confidence in managing obstetric risks in home births and with maternal caregivers’ beliefs about safety of home births [33]. Other interesting outcomes related to preferred place of birth and risk perception have been found as well.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since 9–13 percent of women who intend to deliver at home require hospital transfer where inter‐professional communication is a determinant of patient outcomes, it is critical to learn more about provider beliefs . A Canadian study found that 84 percent of the variance in attitudes toward home birth could be accounted for by type of maternity provider, with obstetricians having the least favorable attitudes, midwives having the most favorable attitudes, and family practitioners falling in between . Another paper describing results from the same study found that midwives generally believed home births to be safe, while physicians were diametrically opposed .…”
mentioning
confidence: 99%
“…Similarly to previous publications [1,4], we found the risk of perinatal mortality to be up to 3 folds higher in out-of-hospital deliveries compared with in-hospital deliveries. While elective home birth as a pre-planned event attended by trained midwives and physicians may have comparable outcomes to planned in-hospital birth [10][11][12][13], the accidental, un-intended out-of-…”
Section: Discussionmentioning
confidence: 99%